Analisis Al-Mubalaghah Pada Ayat-Ayat Hiperbola Dalam Surah Al-Zalzalah (Studi Analisis Ilmu Badi’) - Ardea Pramesti; Robbi Rehan Candra; Harun Alrasyid (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article aims to analyze the use of Al-Mubalaghah in Surah Al-Zalzalah from the perspective of the science of badi'. Al-Mubalaghah, as one of the rhetorical styles in the Qur'an, is used to emphasize certain meanings by exaggerating or magnifying the state being described. This study employs a qualitative research methodology, where the data are obtained through a literature review followed by a descriptive analysis method, which involves presenting or explaining facts clearly and in detail, followed by further analysis. The analysis results indicate that in Surah Al-Zalzalah, there are two types of Al-Mubalaghah found in four verses: the type of Al-Mubalaghah called Tabligh in verses 1 and 2, and Al-Mubalaghah called Ighraq in verses 4 and 6. These rhetorical devices serve to emphasize the magnitude of the event of the Day of Judgment, illustrate the extraordinary effects of the earthquake that shakes the world, and create a strong dramatic impression of the event. Thus, this study provides a deeper understanding of the rhetorical techniques used in the Qur'an and their application in the interpretation of badi' science.